Minor effects of green tea catechin supplementation on cardiovascular risk markers in active older people: A randomized controlled trial. Issue 3 (5th October 2012) - Miyazaki, Ryo; Kotani, Kazuhiko; Ayabe, Makoto; Tsuzaki, Kokoro; Shimada, Junko; Sakane, Naoki; Takase, Hideto; Ichikawa, Hiroshi; Yonei, Yoshikazu; Ishii, Kojiro
<x xml:space="preserve">Abstract</x> Aim: Although previous studies have shown that consumption of green tea catechins (GTC) and walking might prevent development of cardiovascular disease (CVD), the effects of GTC supplementation on CVD risk in active older people are unknown. Methods: A total of 52 older adults (male/female 20/32, mean age 69.1 ± 5.9 years) participating in a pedometer‐based walking program were randomly assigned to a GTC group with an intake of 630.9 mg GTC daily (n = 26) or a control group (n = 26) for 14 weeks. Cardiovascular risk markers were measured before and after this trial. Results: In the GTC group, values of the following markers were significantly reduced (P < 0.05) from the beginning to the end of the trial: waist circumference (from 84.2 ± 8.4 to 82.2 ± 8.5 cm), hip circumference (from 95.1 ± 6.9 to 92.2 ± 6.3 cm), total cholesterol (from 233.0 ± 46.3 to 218.8 ± 42.3 mg/dL), low‐density lipoprotein cholesterol (from 130.4 ± 36.2 to 119.1 ± 33.4 mg/dL) and low‐density lipoprotein cholesterol to high‐density lipoprotein cholesterol ratio (from 2.0 ± 1.7 to 1.7 ± 0.5); only hip circumference (from 95.6 ± 8.1 to 94.1 ± 7.6 cm) was significantly reduced (P < 0.05) in the control group. No significant between‐group differences were found for any parameter measured. Conclusions: Although GTC might reduce cholesterol levels, the present randomized control trial suggests that GTC supplementation in active older participants did not significantly affect cardiovascular risk markers. Future studies should identify more effective combinations of GTC supplementation and physical activity. Geriatr Gerontol Int 2013; 13: 622–629.